Pengujian Blackbox pada Aplikasi Penyimpanan berbasis Android menggunakan Teknik Boundary Value Analysis - Gita Fadila Fitriana; Wildan Eri Saputra; Rifki Adhitama (Politeknik Negeri Cilacap, 2021)
Mobile app or commonly known as an application on a smartphone is one of the businesses that is currently being developed by many people to meet human needs in many ways. Mobile apps are very widely used because they are easy and almost everyone in Indonesia already has a smartphone. Of the various applications made to facilitate human work, one of which is the application of inventory or storage and recording related to assets or goods that are very important in an organization or company so that in the development of their business they can be analyzed at any time. However, every application creation cannot be separated from testing the application to overcome errors that occur when the application is used. To overcome and look for bugs and errors contained in the application, a test was made on the storage application using the black box testing method with the boundary value analysis (BVA) technique. BVA is one of the tests to find errors in applications from the user's point of view by testing the limit values at the upper and lower limits with the stages of identifying problems, selecting test data, test data, testing using boundary value analysis and also documentation. The results of the study using boundary value analysis as a whole have a success percentage of the application after testing is 5:1 with a success rate of 83.33%.